Trade openness, market competition, and inflation: Some sectoral evidence from OECD countries - Mahir Binici; Yin-Wong Cheung; Kon S. Lai (Center for Economic Studies and ifo Institute (CESifo), 2011)
This study evaluates the role market competition plays in determining inflation based on sector-level data from OECD countries. In theory, trade openness can affect inflation through changes in market competitiveness and productivity. Nonetheless, previous empirical studies often fail to account for productivity effects, and their results may overstate the role of market competition. This study shows that inflation decreases with greater market competitiveness even after controlling for productivity effects. Indeed, when market competition and productivity effects are both accounted for, trade openness becomes insignificant in explaining inflation. The results support that changes in market competitiveness and productivity are the main channels through which trade openness affects inflation.
Keywords: C23; E31; L16; 330; trade openness; inflation; market structure; static panel; dynamic panel; Inflation; Politik der offenen Tür; Außenhandelsliberalisierung; Branche; Wettbewerb; Marktstruktur; Produktivität; Schätzung; OECD-Staaten